NMR mapping of RANTES surfaces interacting with CCR5 using linked extracellular domains. (2nd April 2013) - Schnur, Einat; Kessler, Naama; Zherdev, Yuri; Noah, Eran; Scherf, Tali; Ding, Fa‐Xiang; Rabinovich, Svetlana; Arshava, Boris; Kurbatska, Victoria; Leonciks, Ainars; Tsimanis, Alexander; Rosen, Osnat; et al.
<x xml:space="preserve">Abstract</x> Chemokines constitute a large family of small proteins that regulate leukocyte trafficking to the site of inflammation by binding to specific cell‐surface receptors belonging to the G‐protein‐coupled receptor (GPCR) superfamily. The interactions between N–terminal (Nt‐) peptides of these GPCRs and chemokines have been studied extensively using NMR spectroscopy. However, because of the lower affinities of peptides representing the three extracellular loops (ECLs) of chemokine receptors to their respective chemokine ligands, information concerning these interactions is scarce. To overcome the low affinity of ECL peptides to chemokines, we linked two or three CC chemokine receptor 5 (CCR5) extracellular domains using either biosynthesis in Escherichia coli or chemical synthesis. Using such chimeras, CCR5 binding to RANTES was followed using 1H‐15N‐HSQC spectra to monitor titration of the chemokine with peptides corresponding to the extracellular surface of the receptor. Nt‐CCR5 and ECL2 were found to be the major contributors to CCR5 binding to RANTES, creating an almost closed ring around this protein by interacting with opposing faces of the chemokine. A RANTES positively charged surface involved in Nt‐CCR5 binding resembles the positively charged surface in HIV‐1 gp120 formed by the C4 and the base of the third variable loop of gp120 (V3). The opposing surface on RANTES, composed primarily of β2–β3 hairpin residues, binds ECL2 and was found to be analogous to a surface in the crown of the gp120 V3. The chemical and biosynthetic approaches for linking GPCR surface regions discussed herein should be widely applicable to the investigation of interactions of extracellular segments of chemokine receptors with their respective ligands.